Uno sguardo oltre lâ€™architettura per la detenzione PrisON: unâ€™ipotesi di ricerca per il carcere aperto (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
This project has two primary, interrelated, goals: the first one is to develop new methodological and intellectual tools to intervene on prison architecture defining a new prison architectural model; the second one is to revitalize the literature on prison conditions. This study is guided by the idea to advance, innovate and improve the heavy prison living condition. This goal can be developed through an interdisciplinary approach defining a new typology of prison. The research assumptions are: (1) define the qualified characters of the prison space increasing the efficiency of the rehabilitation of the detainees; (2) a good governance requires an architectural space that correspond to the optimization of uses and functions; (3) the need of a new and upgraded typology of prison architecture more respectfull of human right and finalized to rehabilitate the detainees to come back into society. By placing the quality of living of the detainees and the importance of the rehabilitation in a new prison architecture at the center of this project, the research starts analysing the condition of the prison in Italy, and expand the analysis elsewhere for selecting the best examples of prisons in the world. In parallel this study develops also an empirically grounded theoretical framework that is able to overcome the consolidated approaches in defining a new prison architecture. Therefore the research will significantly reorient the way prison architecture has been usually investigated and built. The final scope would be to edit a manual resuming how to intervene on the existing prisons and how to design new prison architecture, involvingÂ  multidisciplinary competences that could guarantee advanced intellectual conditions.Â